Synergistic Impact of Body Mass Index and Cognitive Function on All-Cause Mortality in Older Adults: A Nationwide Longitudinal Study - Han, Ke; Jia, Wangping; Wang, Shengshu; Cao, Wenzhe; Song, Yang; Wang, Jianwei; Liu, Miao; Yang, Shanshan; He, Yao (Frontiers in Endocrinology, 2021)
Background Body mass index (BMI) and cognitive function are independent predictors of mortality risk. However, little is known about the combined impact of BMI and cognitive function on the risk of all-cause mortality in older adults. In this study, we aimed to examine the associations between BMI, cognitive function, and all-cause mortality, including between-factor interactions, in the general population of older adults in China. Methods We used the data between 2011 and 2018 from the Chinese Longitudinal Healthy Longevity Survey that included adults aged ≥65 years residing in the 23 provinces of China. The association between BMI and cognitive function on all-cause mortality was examined with the Cox proportional hazards regression model. Results The study included 8,293 Chinese older adults. Low BMI (underweight) and cognitive impairment were associated with the highest risk of death after adjustments [hazard ratio (HR) = 2.18; 95% confidence interval (CI), 1.96–2.41]; this combined effect was more prominent among adults aged <100 years and women. In addition, there was an interaction effect of BMI and cognitive impairment on all-cause mortality (P <0.001). Concurrently, among older adults with normal cognition, the risk of mortality related to underweight was higher than among their cognitively impaired counterparts [55% (normal cognition) vs. 38% (cognitive impairment)]. Conclusions Low BMI (underweight) and cognitive impairment were independently and jointly associated with increased risk of all-cause mortality among Chinese older adults, and females showed a stronger effect in this association. The association between BMI and mortality was more pronounced in the participants with normal cognition than in their cognitively impaired counterparts.